Peroxisome proliferator-activated receptor-α-mediated transcription of miR-301a and miR-454 and their host gene SKA2 regulates endothelin-1 and PAI-1 expression in sickle cell disease - Gonsalves, Caryn S.; Li, Chen; Malik, Punam; Tahara, Stanley M.; Kalra, Vijay K. (Bioscience reports, 2015)
Endothelin-1 (ET-1) and plasminogen activator inhibitor-1 (PAI-1) play important roles in pulmonary hypertension (PH) in sickle cell disease (SCD). Our previous studies show higher levels of placenta growth factor (PlGF) in SCD correlate with increased plasma levels of ET-1, PAI-1, and other physiological markers of PH. PlGF-mediated ET-1 and PAI-1 expression occurs via activation of hypoxia-inducible factor-1α (HIF-1α). However, relatively little is understood regarding post-transcriptional regulation of PlGF-mediated expression of ET-1 and PAI-1. Herein, we show PlGF treatment of endothelial cells reduced levels of miR-301a and miR-454 from basal levels. In addition, both miRNAs targeted the 3′-UTRs of ET-1 and PAI-1 mRNAs. These results were corroborated in the mouse model of SCD [Berkeley sickle mice (BK-SS)] and in SCD subjects. Plasma levels of miR-454 in SCD subjects were significantly lower compared with unaffected controls, which correlated with higher plasma levels of both ET-1 and PAI-1. Moreover, lung tissues from BK-SS mice showed significantly reduced levels of pre-miR-301a and concomitantly higher levels of ET-1 and PAI-1. Furthermore, we show that miR-301a/miR-454 located in the spindle and kinetochore-associated protein-2 (SKA2) transcription unit was co-transcriptionally regulated by both HIF-1α and peroxisome proliferator-activated receptor-α (PPAR-α) as demonstrated by SKA2 promoter mutational analysis and ChIP. Finally we show that fenofibrate, a PPAR-α agonist, increased the expression of miR-301a/miR-454 and SKA2 in human microvascular endothelial cell line (HMEC) cells; the former were responsible for reduced expression of ET-1 and PAI-1. Our studies provide a potential therapeutic approach whereby fenofibrate-induced miR-301a/miR-454 expression can ameliorate PH and lung fibrosis by reduction in ET-1 and PAI-1 levels in SCD.